Pattern recognition applications and methods : International Conference, ICPRAM 2013, Barcelona, Spain, February 15-18, 2013, Revised selected papers /: International Conference, ICPRAM 2013, Barcelona, Spain, February 15-18, 2013, Revised selected papers. (2015) - Unknown
No abstract available